Recepcja konfucjanizmu we współczesności - Klityńska, Pamela (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2016)
The purpose of the article is to discuss issues concerning the penetration of Confucian doctrine to the modern culture of China. The author states that Confucius is the most outstanding thinker not only of his times, but also of the present world. Confucianism is the basis for action not only for the society but also for China as a country. This work is an attempt to prove that society is still essentially based on the principles proposed to them by Confucius. Moreover it is also an attempt to explain why the Chinese put so much resistance to the culture coming from the West. This article is not focused only on China – it includes issues of other countries, where Confucianism is visible
Keywords: Confucius (551-479 a.C.); konfucjanizm; filozofia; Chiny; współczesność bhuu